2006
DOI: 10.2215/cjn.01651105
|View full text |Cite
|
Sign up to set email alerts
|

Presensitization

Abstract: Much attention has been placed recently on transplantation in highly HLA-sensitized patients. In attempts to remove these antibodies and enable successful transplantation, several novel approaches have been developed. These include intravenous Ig (IVIg), mycophenolate mofetil, sirolimus, alemtuzumab, protein A immunoabsorption, and rituximab. IVIg has emerged as a very effective agent when used alone in high dose or when used in low dose and combined with plasmapheresis. Although alemtuzumab has been used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 63 publications
5
73
0
4
Order By: Relevance
“…Candidate recipients with pre-existing antibodies to potential donor grafts have a higher risk of rejection and eventually graft loss (1)(2)(3)(4)(5)(6). It is commonly accepted that these antibodies are either naturally pre-formed or had developed after exposure to allogeneic antigens occurring during pregnancy, blood transfusion or previous allografts.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate recipients with pre-existing antibodies to potential donor grafts have a higher risk of rejection and eventually graft loss (1)(2)(3)(4)(5)(6). It is commonly accepted that these antibodies are either naturally pre-formed or had developed after exposure to allogeneic antigens occurring during pregnancy, blood transfusion or previous allografts.…”
Section: Introductionmentioning
confidence: 99%
“…IVIg are also useful for pretransplantation desensitization of patients who have high levels of preformed anti-HLA antibodies and are awaiting renal transplantation (3) and, in combination with plasmapheresis, for the treatment of acute humoral rejection (4,5). Recently, our group also reported that the use of IVIg as a prophylactic therapy in patients at high immunologic risk was associated with good 1-yr outcome and a profound decrease in level of panel reactive antibodies (6).…”
mentioning
confidence: 99%
“…Campath is a humanized mAb against CD52, a small glycosylphosphatidylinositol-anchored glycoprotein determinant that is highly expressed on both T and B cells. However, despite its reactivity against B cells, it has been unable to prevent and in fact may result in increased rates of C4d-positive acute humoral rejections (20). Our patient, in November 2003, 4 months after his renal transplant, had normal or slightly increased number of circulating B cells (34%, with an absolute count 126/lL) despite lymphopenia (total lymphocytes 7%, with a normal range of 15-50%).…”
Section: Remuzzi Used Rituximab Infusions (375 Mg/mmentioning
confidence: 63%